The Effect of Surface Compliance n Knee Joint Loads During Level and Decline Running - Casadonte, Joey (East Carolina University)
Running is known for providing numerous health benefits that untimely leads to decreased cardiac mortality. Despite these health benefits, running can cause overuse injuries in up to 79% of runners with a high incidence rate occurring in the knee¹,². Decline running in particular is associated with increased GRFs, resulting in increased knee contact forces. While decreased surface stiffness can result in increased leg stiffness in level running, it is difficult to determine how a softer surface would affect the knee joint in a decline setting. We predict a softer running surface would cause a reduction in knee joint loads during decline running because the runner's momentum would be directed more along the surface in decline running than level running. Therefore, we hypothesized that decreasing surface stiffness in decline running would result in a reduction in knee joint loads. The purpose of this study was to test the effect surface stiffness has on the knee joint loads in decline and level running in order to help prevent injury in runners. 14 healthy recreational runners provided written informed consent to university approved procedures. Knee joint patello-femoral compression and tibio-femoral compression and shear forces were modelled from GRFs and kinematics during 10[degree] decline and level running at a mean speed of 3.2 ms⁻¹. Participants ran with and without a 3 cm thick polyvinyl chloride (PVC) sponge shock absorbing mat (closed cell, Shore 00 65) places along the entire runway. Maximum forces were analyzed with 2-way ANOVA followed by Schefe post hoc tests, all p[less-than]0.05. Decline running on the softer surface lower the A/P GRF 56%, the patello-femoral compression, tibio-femoral compression, and shear forces 15%, 6%, 15% compared to the stiffer decline condition (p[less-than]0.05). Surface stiffness had no effect on these forces in level running (p>0.18). Inclination angle and surface stiffness had no effect on maximum GRF. We predict the mat reduced knee forces in decline because the initial impact between the runner and the surface was more in line with the surface in decline, producing a larger displacement of the mat material in decline when compared to level. We demonstrated that reducing surface stiffness can reduce knee loads during decline running at a 10[degree] decline. Further, we found that the same decrease in surface stiffness had no effect on knee joint loads in level running. This interaction shows how there is a need for further analysis when investigating running biomechanics by investigating more than one setting and surface.
Keywords: Running injuries--Prevention; Long-distance running--Training